Sexuality Education: Emerging Trends in Evidence and Practice - Haberland, Nicole; Rogow, Deborah (Journal of Adolescent Health, 2015)
The International Conference on Population and Development and related resolutions have repeatedly called on governments to provide adolescents and young people with comprehensive sexuality education (CSE). Drawing from these documents, reviews and meta-analyses of program evaluations, and situation analyses, this article summarizes the elements, effectiveness, quality, and country-level coverage of CSE. Throughout, it highlights the matter of a gender and rights perspective in CSE. It presents the policy and evidence-based rationales for emphasizing gender, power, and rights within programs—including citing an analysis finding that such an approach has a greater likelihood of reducing rates of sexually transmitted infections and unintended pregnancy—and notes a recent shift toward this approach. It discusses the logic of an “empowerment approach to CSE” that seeks to empower young people—especially girls and other marginalized young people—to see themselves and others as equal members in their relationships, able to protect their own health, and as individuals capable of engaging as active participants in society.